Design Issues for a Dexter-based Hypermedia System - Grønbæk, Kaj; Trigg, Randall H. (DAIMI Report Series, 1993)
This paper discusses experiences and lessons learned from the design of an open hypermedia system, one that integrates applications and data not ’’owned’’ by the hypermedia. The Dexter Hypertext Reference Model was used as the basis for the design. Though our experiences were generally positive, we found the model constraining in certain ways and underdeveloped in others. For instance, Dexter argues against dangling links, but we found several situations where permitting and supporting dangling links was advisable. In Dexter, the data objects making up a component’s contents are encapsulated in the component; in practice, references to objects stored apart from the hyper media structure should be allowed. We elaborate Dexter’s notion of composite component to include composites that ’’contain’’ other components and composites with structured contents, among others. The paper also includes a critique of Dexter’s notion of link directionality, proposes a distinction between marked and unmarked anchors, and discusses anchoring within a composite.